Flow limitations in the iliac arteries in endurance athletes. Current knowledge and directions for the future - Schep, G.; Bender, M. H.; Kaandorp, D.; Hammacher, E.; de Vries, W. R. (International Journal of Sports Medicine, 1999)
Pain and powerless feeling in the leg during cycling may indicate a serious problem that limits the performance in cyclists. Apart from the well-known muscular and neurological origin, such complaints can also be attributed to flow limitations in the iliac arteries caused by functional lesions (kinking and/or excessive length of vessels) and/or intravascular lesions (endofibrosis). Reliable insight in the prevalence is lacking. Most intravascular lesions (approximately 90%) are located in the external iliac artery. The diagnosis is frequently missed because physiotherapists and medical doctors are often unacquainted with the problem. The only finding in physical examination, discriminating for a vascular problem, is a bruit in the inguinal region with the thigh maximally flexed. Available diagnostic techniques are proven to be inadequate for this specific lesion, which has characteristics other than those of atherosclerotic lesions. Moreover, common techniques in a vascular laboratory do not incorporate the specific sport conditions necessary for provoking the complaints. Provocative testing on a bicycle ergometer with high intensity of exercise, combined with postexercise blood pressure measurements (at the ankle of both legs, or the ankle to arm pressure ratio) is used. Imaging techniques (echo-doppler, arterial digital subtraction angiography, magnetic resonance imaging and angiography) are necessary for proper classification of the problem. The application of specific provoking manoeuvres (hip flexion, psoas contraction, high-intensity exercise) in combination with these imaging techniques prove to be potentially valuable, although the diagnostic accuracy has to be established. Treatment should be tailored to the specific problems of the individual patient. Conservative treatment mainly indicates an advice to change sports activity. Surgical mobilization of the iliac arteries for functional lesions, and vascular reconstructions in case of intravascular lesions are possible, although long-term follow-up is lacking. Percutaneous transluminal angioplasty and intravascular stent are contra-indicated because of high risks for dissection and reactive intimal hyperplasia, respectively.